Aquatic toxicology and environmental fate. - Poston, Ted M.; Purdy, Rich (Philadelphia, P.A. American Society for Testing and Materials, 1986)
ASTM STP 921
Keywords: Water -- Pollution -- Environmental aspects -- Congresses; Water -- Pollution -- Toxicology -- Congresses; Water quality bioassay -- Congresses